2011
DOI: 10.1088/1748-9326/6/4/045208
|View full text |Cite
|
Sign up to set email alerts
|

Wildfires in northern Siberian larch dominated communities

Abstract: The fire history of the northern larch forests within the permafrost zone in a portion of northern Siberia (∼66 • N, 100 • E) was studied. Since there is little to no human activity in this area, fires within the study area were mostly caused by lightning. Fire return intervals (FRI) were estimated on the basis of burn marks on tree stems and dates of tree natality. FRI values varied from 130 to 350 yr with a 200 ± 50 yr mean. For southerly larch dominated communities, FRI was found to be shorter (77 ± 20 yr a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 22 publications
8
78
4
1
Order By: Relevance
“…Our ecotone-level estimates of fire rotation are similar to the mean fire return interval calculated for Siberia's northern sparse forests (227-556 yr, mean = 357 yr) from AVHRR satellite data (Soja et al, 2006). Furthermore, they are similar to dendrochronological estimates of fire return interval along the forest-tundra ecotone in central Siberia (130-350 yr, mean = 200 ± 50 yr) (Kharuk et al, 2011). Our fire rotation estimate for the mountain larch forests (64.5-67 • N) was slightly greater than the fire return interval determined for larch-dominated communities (∼ 64 • N) in central Siberia (Kharuk et al, 2008(Kharuk et al, , 2011, potentially due to slightly cooler temperatures and less human disturbance of the landscape.…”
Section: Fire Regime Along the Forest-tundra Ecotone In Northeastern supporting
confidence: 78%
See 2 more Smart Citations
“…Our ecotone-level estimates of fire rotation are similar to the mean fire return interval calculated for Siberia's northern sparse forests (227-556 yr, mean = 357 yr) from AVHRR satellite data (Soja et al, 2006). Furthermore, they are similar to dendrochronological estimates of fire return interval along the forest-tundra ecotone in central Siberia (130-350 yr, mean = 200 ± 50 yr) (Kharuk et al, 2011). Our fire rotation estimate for the mountain larch forests (64.5-67 • N) was slightly greater than the fire return interval determined for larch-dominated communities (∼ 64 • N) in central Siberia (Kharuk et al, 2008(Kharuk et al, , 2011, potentially due to slightly cooler temperatures and less human disturbance of the landscape.…”
Section: Fire Regime Along the Forest-tundra Ecotone In Northeastern supporting
confidence: 78%
“…Subdividing the ecotone into southern mountain larch forests and northern lowland forest-tundra revealed that fire rotation differed sevenfold between these two zones (110 vs. 792 yr). This spatial pattern of fire activity is similar to that observed across Siberia, with fire return interval generally increasing from south to north (Furyaev et al, 2001;Soja et al, 2004;Kharuk et al, 2011) and correlated with both summer temperatures and AGB (Furyaev et al, 2001). Our ecotone-level estimates of fire rotation are similar to the mean fire return interval calculated for Siberia's northern sparse forests (227-556 yr, mean = 357 yr) from AVHRR satellite data (Soja et al, 2006).…”
Section: Fire Regime Along the Forest-tundra Ecotone In Northeastern supporting
confidence: 78%
See 1 more Smart Citation
“…In Siberian larch forest, the fire regimes can be highly localized, contingent on soil moisture, permafrost status, and understory vegetation characteristics. For example, both satellite and dendrochronological data have shown that fire return interval is generally longer in northern regions (Kharuk et al 2011) and northeast-facing slopes (Kharuk et al 2008). Therefore, higher solar radiation and more frequent fire could promote the permafrost thaw and drainage on southwest-facing slopes.…”
Section: Comparison With Other Studies On Larch Forestsmentioning
confidence: 99%
“…Пространственная структура оползней неоднородна относительно азимута: все оползни локализованы на склонах южной и юго-западной экспозиции; ни один оползень не обнаружен стом напочвенного покрова в виде мхов и лишайников, действующих в качестве теплоизолято-ра [32]. В аномально тёплые годы наблюдается оттаивание почвогрунтов выше среднегодовых показателей, что приводит к потере сцепления корней с глубьлежащими слоями почвогрунтов.…”
Section: оползни и рельеф территорииunclassified